Communication—Dissolution and Passivation of a Ni-Cr-Fe-Ru-Mo-W High Entropy Alloy by Elementally Resolved Electrochemistry. Issue 6 (23rd March 2020) - Li, Xuejie; Han, Junsoo; Lu, Pin; Saal, James E.; Olson, Gregory B.; Frankel, Gerald S.; Scully, John R.; Ogle, Kevin
Abstract : The formation and dissolution of the passive film on a novel NiCrFeRuMoW high entropy alloy in H2 SO4 was measured with atomic emission spectroelectrochemistry. Passivation involved Cr and Ru enrichment, whether passivation was achieved spontaneously at open circuit or by potentiostatic step into the passive domain. The other elements, Ni, Fe, Mo, and W, dissolved at rates approximately proportional to their bulk concentrations. The air formed film showed only a Cr enrichment. Excellent corrosion resistance properties were indicated by spontaneous passivation, the low passive current in the polarization curve, and the absence of detectable elemental dissolution during the active peak.